For extra credit I have to show that: -5/39 sin8x sin5x - 8/39 cos8x cos5x = -cos13x/26 - cos3x/6. Any suggestions on where to start? Thanks for the help.
Follow Math Help Forum on Facebook and Google+
Originally Posted by Carol For extra credit I have to show that: -5/39 sin8x sin5x - 8/39 cos8x cos5x = -cos13x/26 - cos3x/6. Any suggestions on where to start? Thanks for the help. From the compound angle formulae: $\displaystyle \sin x \sin y = \frac{\cos(x - y) - \cos (x + y)}{2}$ $\displaystyle \cos x \cos y = \frac{\cos(x - y) + \cos (x + y)}{2}$
View Tag Cloud